Preparation method of non-plasticized solid calcium ion selective electrode

By using conductive polyaniline and soluble conductive polyaniline layers in solid calcium ion selective electrodes, combined with ultraviolet light-induced polymerization technology, a plasticized solid calcium ion selective electrode was prepared, solving the problems of potential drift and plasticizer leakage. , achieving stable and accurate calcium ion detection.

CN119246643APending Publication Date: 2025-01-03CHINA TOBACCO HENAN IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411425271.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing solid-state ion-selective electrodes are prone to aqueous layers between the solid-state contact layer and the ion-selective membrane, resulting in potential drift, and traditional electrodes require the use of plasticizers, resulting in potential instability and sample contamination.

Method used

Conductive polyaniline is used as the solid contact layer, and a layer of soluble conductive polyaniline is wrapped with a drip-coated acrylate calcium ion sensitive film solution is applied to it, and polymerization is initiated by ultraviolet light to prepare a plasticized solid calcium ion-selective electrode.

Benefits of technology

The electrode preparation with anhydrous layer interference and plasticizer leakage is achieved, which improves the stability of potential response and measurement accuracy, conforms to the Nernst equation, and is suitable for calcium ion detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119246643A_ABST
    Figure CN119246643A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of tobacco water treatment, and particularly relates to a preparation method of a non-plasticization solid calcium ion selective electrode, which comprises the following steps: firstly, pretreating an electrode, activating a glassy carbon electrode in an H2SO4 solution, and then immersing the glassy carbon electrode in a mixed solution of potassium ferricyanide and potassium cyanide to complete pretreatment of the glassy carbon electrode, so as to obtain the non-plasticization solid calcium ion selective electrode. Secondly, in order to prepare a solid contact layer, putting the pretreated glassy carbon electrode into an aniline hydrochloride solution, electrically depositing polyaniline on the glassy carbon electrode, dipping a soluble conductive polyaniline saturated solution, and drying in a crucible containing sand through a dryer; and 3, preparing a calcium ion sensitive membrane, dispensing a calcium ion sensitive membrane solution on the surface of the glassy carbon electrode, and curing the calcium ion sensitive membrane under the irradiation of an ultraviolet lamp to prepare the all-solid-state calcium ion selective electrode. The electrode is an ion selective electrode without water layer interference and plasticizer leakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tobacco water treatment, and in particular relates to a method for preparing a non-plasticized solid calcium ion selective electrode. Background Art

[0002] Calcium ion, as one of the important ions in soil and water, is not only an important component of the operation of the ecosystem, but also has an important impact on the survival of all organisms. The detection methods for calcium ion content generally include spectrophotometry, ion chromatography, titration, etc. However, the above methods have disadvantages such as high detection cost, slow detection speed, and complex detection steps, and cannot achieve real-time monitoring on site. Electrochemical sensors are widely used due to their advantages such as easy portability, low cost, and fast response speed.

[0003] As an electrochemical sensor, solid-state ion-selective electrodes have been widely used in the fields of healthcare, food safety, pollution monitoring, and environmental monitoring. However, a water layer often appears between the solid contact layer and the ion-selective membrane of the solid-state ion-selective electrode, which causes potential drift and inaccurate measurement results. At the same time, traditional solid-state ion-selective electrodes mostly use polyvinyl chloride (PVC) as the base membrane of the electrode, but electrodes with PVC as the base membrane must be added with plasticizers to produce the Nernst effect. Although PVC is soluble in a variety of plasticizers, plasticizer leakage will occur with the use of the electrode, which not only affects the stability of the potential, but also contaminates the sample. Therefore, it is necessary to prepare an ion-selective electrode without water layer interference and plasticizer leakage. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a non-plasticized solid calcium ion selective electrode to solve the problems existing in the above-mentioned background technology.

[0005] To achieve the above objectives, this application is implemented through the following technical solutions:

[0006] A method for preparing a non-plasticized solid calcium ion selective electrode comprises the following steps:

[0007] S1. Electrode pretreatment:

[0008] The glassy carbon electrode was activated by cyclic voltammetry in a 0.5-1 mol / L H2SO4 solution using an electrochemical workstation, with a scanning range of -1-1V, until a stable cyclic voltammogram was obtained; the activated glassy carbon electrode was used as a working electrode, and a Pt wire electrode and an Ag / AgCl electrode were used as a counter electrode and a reference electrode, respectively, and immersed in a mixed solution of 1 mol / L potassium ferrocyanide and 1 mol / L potassium cyanide, and scanned by cyclic voltammetry at a scanning speed of 50 mV / s and a scanning range of -1-1V. The electrode could be used only when the peak potential difference was below 80 mV under laboratory conditions;

[0009] S2. Preparation of solid contact layer:

[0010] The working electrode, Pt wire electrode and Ag / AgCl electrode in step S1 are placed in the prepared aniline hydrochloride solution to form a three-electrode system, and polyaniline is electrodeposited on the glassy carbon electrode by cyclic voltammetry at a scan rate of 50 mV / s and a scan range of -1-1 V;

[0011] The glassy carbon electrode after polyaniline deposition is quickly dipped into a saturated solution of soluble conductive polyaniline, and dried in a crucible containing sand in a dryer at 80-100°C for 4-6 hours;

[0012] S3. Preparation of calcium ion sensitive membrane:

[0013] The calcium ion sensitive membrane solution was drop-coated on the surface of the glassy carbon electrode prepared in step S2, and the calcium ion sensitive membrane was photocured using an ultraviolet lamp at a current intensity of 20 A for 20 min, and then dried in a dryer at 80° C. for 4 hours to obtain an all-solid-state calcium ion selective electrode.

[0014] Furthermore, before step S1, the glassy carbon electrode is polished with metallographic sandpaper, impurities attached to the surface are removed with ultrapure water, the glassy carbon electrode is cleaned in an ultrasonic cleaner for a set time and then blown dry with nitrogen, the glassy carbon electrode is polished with alumina slurry, and then cleaned and dried again with ultrapure water.

[0015] Furthermore, the alumina slurry is 0.05 μm alumina slurry.

[0016] Furthermore, the glassy carbon electrode pretreated in step S1 was activated in a 10-2 mol / L CaCl2 solution for 24 hours before use.

[0017] Furthermore, the aniline hydrochloride solution in step S2 is prepared by adding aniline hydrochloride into ultrapure water and then dissolving the aniline hydrochloride by ultrasonication to obtain the aniline hydrochloride solution.

[0018] Furthermore, the soluble conductive polyaniline saturated solution in step S2 is obtained by dissolving a hydrochloric acid-doped copolymer of aniline and 2,5-dimethylaniline in a molar ratio of 5:1-1:1 in N,N-dimethylamide.

[0019] Furthermore, the preparation method of the photocurable calcium ion sensitive film comprises the following steps:

[0020] S31, taking photoinitiator 2,2-dimethoxy-2-phenylacetophenone and 1,6-hexanediol diacrylate, dissolving them in butyl acrylate solution to prepare a photoinitiator solution;

[0021] S32, placing calcium ion carrier IV in a brown reagent bottle, adding the above-mentioned photoinitiator solution and butyl acrylate solution to prepare a calcium ion sensitive membrane solution.

[0022] The beneficial effects of the present invention are:

[0023] The present invention uses conductive polyaniline as a solid contact layer, covers a layer of soluble conductive polyaniline on the surface, then drips an acrylic calcium ion sensitive membrane solution on the soluble conductive polyaniline, and initiates polymerization by ultraviolet light to prepare a novel non-plasticized solid calcium ion selective electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] FIG1 is a non-plasticized calcium ion selective electrode potential response correction curve of a hydrochloric acid-doped copolymer of aniline and 2,5-dimethoxyaniline in a molar ratio of 5:1.

[0025] Figure 2 This is the non-plasticized calcium ion selective electrode potential response correction curve of the hydrochloric acid-doped copolymer of aniline and 2,5-dimethoxyaniline in a molar ratio of 1:1.

[0026] Figure 3 The potential response correction curve of the PVC-based calcium ion selective electrode of the hydrochloric acid-doped copolymer of aniline and 2,5-dimethoxyaniline in a molar ratio of 5:1.

[0027] Figure 4 The potential response correction curve of the PVC-based calcium ion selective electrode of the hydrochloric acid-doped copolymer of aniline and 2,5-dimethoxyaniline in a molar ratio of 1:1.

[0028] Figure 5 Schematic diagram of the structure of the non-plasticized calcium ion selective electrode.

[0029] Figure 6 Schematic diagram of the top view structure of the non-plasticized calcium ion selective electrode.

[0030] Description of reference numerals:

[0031] 1. Glass layer of glassy carbon electrode, 2. Electrodeposited polyaniline layer, 3. Soluble conductive polyaniline layer, 4. Calcium ion selective sensitive membrane layer. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings. The following embodiments are merely exemplary and can only be used to explain and illustrate the technical solution of the present invention, but cannot be construed as limiting the technical solution of the present invention.

[0033] Example 1

[0034] 1) Electrode pretreatment:

[0035] The glassy carbon electrode (GCE) was polished with 2000# metallographic sandpaper, and impurities attached to the surface were removed with ultrapure water. The electrode was cleaned in an ultrasonic cleaner for 5 minutes and then dried with nitrogen. The GCE was polished with 0.05μm alumina slurry, and then cleaned and dried with ultrapure water again. The electrochemical workstation was used to activate the GCE by cyclic voltammetry in a 0.5-1mol / L H2SO4 solution, with a scanning range of -1-1V, until a stable cyclic voltammogram was obtained. The activated GCE was used as the working electrode, and the Pt wire electrode and the Ag / AgCl electrode were used as the counter electrode and the reference electrode, respectively, and immersed in a mixed solution of 1mol / L potassium ferrocyanide and 1mol / L potassium cyanide. The cyclic voltammetry method was used to scan, with a scanning speed of 50mV / s and a scanning range of -1-1V. The peak potential difference was obtained under laboratory conditions and was below 80mV, and the electrode could be used. The electrode was activated in a 10-2mol / L Cacl2 solution for 24 hours before use.

[0036] 2) Preparation of solid contact layer:

[0037] Weigh 3.2397g of aniline hydrochloride into a beaker, add 25ml of ultrapure water, and sonicate for 5 minutes to dissolve the aniline hydrochloride. Place the working electrode, Pt wire electrode, and Ag / AgCl electrode into a three-electrode system in the prepared aniline hydrochloride solution, and use cyclic voltammetry with a scan rate of 50mV / s and a scan range of -1-1V to electrodeposit polyaniline on GCE.

[0038] 35 mg of a hydrochloric acid-doped copolymer of aniline and 2,5-dimethoxyaniline with a molar ratio of 5:1 was weighed and dissolved in N,N-dimethylformamide (DMF) to prepare a saturated solution of soluble conductive polyaniline. The GCE after polyaniline deposition was quickly dipped in the saturated solution of soluble conductive polyaniline and dried in a crucible filled with sand in a dryer at 100°C for 4 hours.

[0039] 3) Preparation of calcium ion sensitive membrane:

[0040] Take 152.4 mg of the photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPP) and 14 μL of 1,6-hexanediol diacrylate (HDDA), dissolve them in 1.1 mL of butyl acrylate (BA) solution to prepare a photoinitiator solution. Weigh 1 mg of calcium ion carrier IV and 0.33 mg of NaTFPB in a brown reagent bottle, add 20 μL of photoinitiator solution and 180 μL of butyl acrylate (BA) solution to prepare a calcium ion sensitive membrane solution. Quickly dip the electrode into the calcium ion sensitive membrane solution, then use an ultraviolet lamp to illuminate the calcium ion sensitive membrane at a current intensity of 20 A for 20 min, dry it in a dryer at 80°C for 4 hours, and after drying, obtain an all-solid-state calcium ion selective electrode.

[0041] Example 2

[0042] 1) Electrode pretreatment:

[0043] The glassy carbon electrode (GCE) was polished with 2000# metallographic sandpaper, and impurities attached to the surface were removed with ultrapure water. The electrode was cleaned in an ultrasonic cleaner for 5 minutes and then dried with nitrogen. The GCE was polished with 0.05μm alumina slurry, and then cleaned and dried with ultrapure water again. The electrochemical workstation was used to activate the GCE by cyclic voltammetry in a 0.5-1mol / L H2SO4 solution, with a scanning range of -1-1V, until a stable cyclic voltammogram was obtained. The activated GCE was used as the working electrode, and the Pt wire electrode and the Ag / AgCl electrode were used as the counter electrode and the reference electrode, respectively, and immersed in a mixed solution of 1mol / L potassium ferrocyanide and 1mol / L potassium cyanide. The cyclic voltammetry method was used to scan, with a scanning speed of 50mV / s and a scanning range of -1-1V. The peak potential difference was obtained under laboratory conditions and was below 80mV, and the electrode could be used. The electrode was activated in a 10-2mol / L Cacl2 solution for 24 hours before use.

[0044] 2) Preparation of solid contact layer:

[0045] Weigh 3.2397g of aniline hydrochloride into a beaker, add 25ml of ultrapure water, and sonicate for 5 minutes to dissolve the aniline hydrochloride. Place the working electrode, Pt wire electrode, and Ag / AgCl electrode into a three-electrode system in the prepared aniline hydrochloride solution, and use cyclic voltammetry with a scan rate of 50mV / s and a scan range of -1-1V to electrodeposit polyaniline on GCE.

[0046] 35 mg of a hydrochloric acid-doped copolymer of aniline and 2,5-dimethoxyaniline in a molar ratio of 1:1 was weighed and dissolved in N,N-dimethylformamide (DMF) to prepare a saturated solution of soluble conductive polyaniline. The ISE after polyaniline deposition was quickly dipped in the saturated solution of soluble conductive polyaniline and dried in a crucible filled with sand in a dryer at 80°C for 6 hours.

[0047] 3) Preparation of calcium ion sensitive membrane:

[0048] Take 152.4 mg of the photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPP) and 14 μL of 1,6-hexanediol diacrylate (HDDA), dissolve them in 1.1 mL of butyl acrylate (BA) solution to prepare a photoinitiator solution. Weigh 1 mg of calcium ion carrier IV and 0.33 mg of NaTFPB in a brown reagent bottle, add 20 μL of photoinitiator solution and 180 μL of butyl acrylate (BA) solution to prepare a calcium ion sensitive membrane solution. Quickly dip the electrode into the calcium ion sensitive membrane solution, then use an ultraviolet lamp to illuminate the calcium ion sensitive membrane at a current intensity of 20 A for 20 min, dry it in a dryer at 80°C for 4 hours, and after drying, obtain an all-solid-state calcium ion selective electrode.

[0049] Comparative Example 1:

[0050] The glassy carbon electrode (GCE) was polished with 2000# metallographic sandpaper, and impurities attached to the surface were removed with ultrapure water. The electrode was cleaned in an ultrasonic cleaner for 5 minutes and then dried with nitrogen. The GCE was polished with 0.05μm alumina slurry, and then cleaned and dried with ultrapure water again. The electrochemical workstation was used to activate the GCE using cyclic voltammetry in a 0.5-1mol / L H2SO4 solution, with a scanning range of -1-1V, until a stable cyclic voltammogram was obtained. The activated GCE was used as the working electrode, and the Pt wire electrode and the Ag / AgCl electrode were used as the counter electrode and the reference electrode, respectively, and immersed in a mixed solution of 1mol / L potassium ferrocyanide and 1mol / L potassium cyanide. The cyclic voltammetry method was used for scanning, with a scanning speed of 50mV / s and a scanning range of -1-1V. The peak potential difference was obtained under laboratory conditions and was below 80mV, and the electrode could be used.

[0051] Weigh 3.2397g of aniline hydrochloride into a beaker, add 25ml of ultrapure water, and sonicate for 5 minutes to dissolve the aniline hydrochloride. Place the working electrode, Pt wire electrode, and Ag / AgCl electrode into a three-electrode system in the prepared aniline hydrochloride solution, and use cyclic voltammetry with a scan rate of 50mV / s and a scan range of -1-1V to electrodeposit polyaniline on GCE.

[0052] Weigh 35 mg of a hydrochloric acid-doped copolymer of aniline and 2,5-dimethoxyaniline with a molar ratio of 5:1 and dissolve it in N,N-dimethylformamide (DMF) to prepare a saturated solution of soluble conductive polyaniline. Quickly dip the ISE after depositing polyaniline into the saturated solution of soluble conductive polyaniline and dry it in a crucible filled with sand in a dryer at 100°C for 4 hours.

[0053] The calcium ion selective membrane (360 mg) component contains 1.3 wt% calcium ion carrier IV (ETH 5234), 0.6 wt% sodium tetrakis (3,5-di (trifluoromethyl) phenyl) borate (NaTFPB), 32.7 wt% polyvinyl chloride (PVC) and 65.4 wt% o-nitrophenyl octyl ether (o-NPOE). The above solution was dissolved in 3 ml tetrahydrofuran (THF) and dried in a dryer at 80 ° C for 6 hours to form a calcium ion selective membrane.

[0054] Comparative Example 2

[0055] The glassy carbon electrode (GCE) was polished with 2000# metallographic sandpaper, and impurities attached to the surface were removed with ultrapure water. The electrode was cleaned in an ultrasonic cleaner for 5 minutes and then dried with nitrogen. The GCE was polished with 0.05μm alumina slurry, and then cleaned and dried with ultrapure water again. The electrochemical workstation was used to activate the GCE using cyclic voltammetry in a 0.5-1mol / L H2SO4 solution, with a scanning range of -1-1V, until a stable cyclic voltammogram was obtained. The activated GCE was used as the working electrode, and the Pt wire electrode and the Ag / AgCl electrode were used as the counter electrode and the reference electrode, respectively, and immersed in a mixed solution of 1mol / L potassium ferrocyanide and 1mol / L potassium cyanide. The cyclic voltammetry method was used for scanning, with a scanning speed of 50mV / s and a scanning range of -1-1V. The peak potential difference was obtained under laboratory conditions and was below 80mV, and the electrode could be used.

[0056] Weigh 3.2397g of aniline hydrochloride into a beaker, add 25ml of ultrapure water, and sonicate for 5 minutes to dissolve the aniline hydrochloride. Place the working electrode, Pt wire electrode, and Ag / AgCl electrode into a three-electrode system in the prepared aniline hydrochloride solution, and use cyclic voltammetry with a scan rate of 50mV / s and a scan range of -1-1V to electrodeposit polyaniline on GCE.

[0057] 35 mg of a hydrochloric acid-doped copolymer of aniline and 2,5-dimethoxyaniline in a molar ratio of 1:1 was weighed and dissolved in N,N-dimethylformamide (DMF) to prepare a saturated solution of soluble conductive polyaniline. The ISE after polyaniline deposition was quickly dipped in the saturated solution of soluble conductive polyaniline and dried in a crucible filled with sand in a dryer at 80°C for 6 hours.

[0058] The calcium ion selective membrane (360 mg) component contains 1.3 wt% calcium ion carrier IV (ETH 5234), 0.6 wt% sodium tetrakis (3,5-di (trifluoromethyl) phenyl) borate (NaTFPB), 32.7 wt% polyvinyl chloride (PVC) and 65.4 wt% o-nitrophenyl octyl ether (o-NPOE). The above solution is dissolved in 3 ml of tetrahydrofuran (THF) and dried in a dryer at 80 ° C for 6 hours to form a calcium ion selective membrane.

[0059] All electrodes were activated in 10-2 mol / L Cacl2 solution for 24 h before testing. The activated GCE was used as the working electrode, and the Pt wire electrode and Ag / AgCl electrode were used as the counter electrode and reference electrode, respectively, to form a three-electrode system for electrochemical testing in Cacl2 solutions of different concentrations (10-7-10-2) mol / L.

[0060] Electrochemical test chart

[0061] Figure 1 The potential response correction curve of the non-plasticized calcium ion selective electrode of the hydrochloric acid doped copolymer of aniline and 2,5-dimethoxyaniline with a molar ratio of 5:1 in the experimental group is shown as a straight line in the figure. The correction equation is y=28.08x+361.119, y represents the response electromotive force, x represents the calcium ion concentration in the solution, the correlation coefficient R2 is 0.986, and the response slope is 28.08. The prepared calcium ion selective electrode conforms to the Nernst equation; Figure 2 The potential response correction curve of the non-plasticized calcium ion selective electrode of the hydrochloric acid doped copolymer of aniline and 2,5-dimethoxyaniline with a molar ratio of 1:1 in the experimental group is shown as a straight line in the figure. The correction equation is y=28.3x+369.197, y represents the response electromotive force, x represents the calcium ion concentration in the solution, the correlation coefficient R2 is 0.990, and the response slope is 28.3. The prepared calcium ion selective electrode conforms to the Nernst equation; Figure 3 The potential response correction curve of the PVC-based calcium ion selective electrode of the hydrochloric acid-doped copolymer of aniline and 2,5-dimethoxyaniline with a molar ratio of 5:1 is shown as a straight line in the figure. The correction equation is y=26.69x+350.069, where y represents the response electromotive force and x represents the calcium ion concentration in the solution. The correlation coefficient R2 is 0.976 and the response slope is 26.69. The prepared calcium ion selective electrode conforms to the Nernst equation. Figure 4The potential response correction curve of the PVC-based calcium ion selective electrode of the hydrochloric acid-doped copolymer of aniline and 2,5-dimethoxyaniline with a molar ratio of 1:1 is shown as the straight line in the figure. The correction equation is y=26.85x+352.797, y represents the response electromotive force, x represents the calcium ion concentration in the solution, the correlation coefficient R2 is 0.979, and the response slope is 26.85. The prepared calcium ion selective electrode conforms to the Nernst equation.

[0062] like Figure 5 Schematic diagram of the structure of the non-plasticized calcium ion selective electrode, glass layer 1 of the glassy carbon electrode, electrodeposited polyaniline layer 2, soluble conductive polyaniline layer 3, and calcium ion selective sensitive membrane layer 4; Figure 6 Schematic diagram of the top view structure of the non-plasticized calcium ion selective electrode, glass layer 1 of the glassy carbon electrode, electrodeposited polyaniline layer 2, soluble conductive polyaniline layer 3, and calcium ion selective sensitive membrane layer 4.

[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a non-plasticized solid calcium ion selective electrode, characterized in that: Use the following steps: S1. Electrode pretreatment: The glassy carbon electrode was activated by cyclic voltammetry in a 0.5-1 mol / L H2SO4 solution using an electrochemical workstation, with a scanning range of -1-1V, until a stable cyclic voltammogram was obtained; the activated glassy carbon electrode was used as a working electrode, and a Pt wire electrode and an Ag / AgCl electrode were used as a counter electrode and a reference electrode, respectively, and immersed in a mixed solution of 1 mol / L potassium ferrocyanide and 1 mol / L potassium cyanide, and scanned by cyclic voltammetry at a scanning speed of 50 mV / s and a scanning range of -1-1V. The electrode could be used only when the peak potential difference was below 80 mV under laboratory conditions; S2. Preparation of solid contact layer: The working electrode, Pt wire electrode and Ag / AgCl electrode in step S1 are placed in the prepared aniline hydrochloride solution to form a three-electrode system, and polyaniline is electrodeposited on the glassy carbon electrode by cyclic voltammetry at a scan rate of 50 mV / s and a scan range of -1-1 V; The glassy carbon electrode after polyaniline deposition is quickly dipped into a saturated solution of soluble conductive polyaniline, and dried in a crucible containing sand in a dryer at 80-100°C for 4-6 hours; S3. Preparation of calcium ion sensitive membrane: The calcium ion sensitive membrane solution was drop-coated on the surface of the glassy carbon electrode prepared in step S2, and the calcium ion sensitive membrane was photocured using an ultraviolet lamp at a current intensity of 20 A for 20 min, and then dried in a dryer at 80° C. for 4 hours to obtain an all-solid-state calcium ion selective electrode.

2. The method for preparing a non-plasticized solid calcium ion selective electrode according to claim 1, characterized in that: Before step S1, the glassy carbon electrode is polished with metallographic sandpaper, impurities attached to the surface are removed with ultrapure water, the glassy carbon electrode is cleaned in an ultrasonic cleaner for a set time and then blown dry with nitrogen, the glassy carbon electrode is polished with alumina slurry, and then cleaned and blown dry again with ultrapure water.

3. The method for preparing a non-plasticized solid calcium ion selective electrode according to claim 2, characterized in that: The alumina slurry is 0.05 μm alumina slurry.

4. The method for preparing a non-plasticized solid calcium ion selective electrode according to claim 1, characterized in that: The glassy carbon electrode pretreated in step S1 was activated in a 10-2 mol / L CaCl2 solution for 24 hours before use.

5. The method for preparing a non-plasticized solid calcium ion selective electrode according to claim 1, characterized in that: The aniline hydrochloride solution in step S2 is prepared by adding aniline hydrochloride into ultrapure water and then dissolving the aniline hydrochloride by ultrasonication to obtain the aniline hydrochloride solution.

6. The method for preparing a non-plasticized solid calcium ion selective electrode according to claim 1, characterized in that: The soluble conductive polyaniline saturated solution in step S2 is obtained by dissolving a hydrochloric acid-doped copolymer of aniline and 2,5-dimethylaniline in a molar ratio of 5:1-1:1 in N,N-dimethylamide.

7. The method for preparing a non-plasticized solid calcium ion selective electrode according to claim 1, characterized in that: The preparation method of the photocurable calcium ion sensitive film comprises the following steps: S31, taking photoinitiator 2,2-dimethoxy-2-phenylacetophenone and 1,6-hexanediol diacrylate, dissolving them in butyl acrylate solution to prepare a photoinitiator solution; S32, placing calcium ion carrier IV in a brown reagent bottle, adding the above-mentioned photoinitiator solution and butyl acrylate solution to prepare a calcium ion sensitive membrane solution.